Optimization of ESP performance through chemical treatment using a single capillary in the Apiay field - Adriana Marcela Duran Pabón; José Alberto Murcia Navas (CT&F Ciencia, Tecnología & Futuro)
The future of production in the Apiay field lies in the T2 formation, although it poses significant challenges, such as high fluid encrustation and heavy crude oil production. These issues have led to strong emulsion problems and operational issues with many wells' electro-submersible pumping systems (ESPs).